2019
DOI: 10.1021/acs.orglett.9b02183
|View full text |Cite
|
Sign up to set email alerts
|

A NaI/H2O2-Mediated Sulfenylation and Selenylation of Unprotected Uracil and Its Derivatives

Abstract: An efficient iodide-catalyzed/hydrogen peroxide mediated sulfenylation and selenylation of unprotected uracil and its derivatives with simple thiols and diselenides was established. This coupling tolerates a broad variety of functional groups to provide diverse 5-sulfur/selenium-substituted uracil derivatives in good to excellent yields (up to 93%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…Hydrogen peroxide is a popular and benign oxidizing agent used in various organic transformations . Recently, Cheng et al have reported hydrogen peroxide-mediated iodide-catalyzed sulfenylation and selenylation of unprotected uracil derivatives . To the best of our knowledge, H 2 O 2 has not been used under additive- and metal-free conditions for the thiocyanation reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide is a popular and benign oxidizing agent used in various organic transformations . Recently, Cheng et al have reported hydrogen peroxide-mediated iodide-catalyzed sulfenylation and selenylation of unprotected uracil derivatives . To the best of our knowledge, H 2 O 2 has not been used under additive- and metal-free conditions for the thiocyanation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently, Cheng et al have reported hydrogen peroxide-mediated iodide-catalyzed sulfenylation and selenylation of unprotected uracil derivatives. 16 To the best of our knowledge, H 2 O 2 has not been used under additive-and metal-free conditions for the thiocyanation reactions. In continuation of our work on new methodology development, 17 we wanted to develop a metal-free thiocyana-…”
Section: ■ Introductionmentioning
confidence: 99%
“…21,22 In our recent communications, we reported a direct, regioselective, and transition-metal-free C−H sulfenylation/ selenylation and O−H boric esterification of unprotected uracil and its derivatives. 23,24 In this paper, we report on the photocatalyzed C−H (hetero)arylations of uracils and practical synthesis of (hetero)arylated uracil bases and nucleosides with diazonium salts (Scheme 1c). This reaction is atom-efficient with N 2 as the sole byproduct and performed in pure water without any transition-metal reagents, avoiding the usage of organic solvents and potential contamination of metallic residues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…根据上述控制实验结果以及已有文献报道, ICl 可 能作为路易斯酸的作用催化杂环化合物芳硒化反应. 与 碘单质催化芳硒化反应类似 [34] , 首先, ICl 作为路易斯酸 催化剂与 PhSeSePh 作用形成 IM1 中间体 [34][35] , 该中间 体接受 4-苯氨基香豆素亲核进攻 [36] , 最终获得预期的目 标产物(Scheme 3).…”
unclassified